Regioselective Formation of Acrolein-derived Cyclic 1,N(2)-Propanodeoxyguanosine Adducts Mediated by Amino Acids, Proteins, and Cell Lysates - Chung, Fung-Lung (2012)
Acrolein (Acr) is a major component in cigarette smoke and a ubiquitous environmental pollutant. It is also formed as a product of lipid peroxidation. Following ring closure via the Michael addition, Acr modifies deoxyguanosine (dG) in DNA by forming cyclic 1,N(2)-propanodeoxyguanosine adducts (OHPdG). The reactions of Acr with dG yield, depending on the direction of ring closure, two regioisomers, α- and γ-OHPdG, in approximately equal amounts. However, previous (32)P-postlabeling studies showed that the γ isomers were detected predominantly in DNA of rodent and human tissues. Because of the potential differential biological activity of the isomeric OHPdG adducts, it is important to confirm and study the chemical basis of the regioselective formation of γ isomers in vivo. In this study, it is confirmed that γ-OHPdG adducts are indeed the major isomers formed in vivo as evidenced by a LC-MS/MS method specifically developed for Acr-derived dG adducts. Furthermore, we have shown that the formation of γ-isomers is increased in the presence of amino-containing compounds, including amino acids, proteins, and cell lysates. A product of Acr and arginine that appears to mediate the regioselective formation of γ isomers was identified, but its structure was not fully characterized due to its instability. This study demonstrates that intracellular amino-containing compounds may influence the regiochemistry of the formation of OHPdG adducts and reveals a mechanism for the preferential formation γ-OHPdG by Acr in vivo.